Resilient routing in optical networks using SRLG-disjoint path pairs of min-sum cost - Gomes, Teresa (2013)
Ensuring network survivability is of the utmost importance in today's networks. A Shared Risk Link Group (SRLG) is the set of links in the network that share a common physical resource subject to fault(s). This concept allows an upper layer the ability to implement SRLG diverse routing. Two algorithms, the Conflicting SRLG Exclusion (CoSE) and the Iterative Modified Suurballe's Heuristic (IMSH), will be shortly reviewed. The first solves the min-min problem and the second the min-sum problem, considering SRLG-disjoint paths. It will then be described a new version of CoSE, which will be designated as CoSE-MS, for solving the min-sum problem for SRLG diverse routing. Finally CoSE-MS and IMSH performance will be compared using random networks and an optical network. Results show that CoSE-MS is a good compromise between the quality of obtained solutions and the used CPU time.